The Voice of God in the text of scripture : explorations in constructive dogmatics - Los Angeles Theology Conference (4th: 2016: Biola University); Crisp, Oliver D., ed.; Sanders, Fred, ed.; Abraham, William J. (Grand Rapids, Michigan : Zondervan, 2016)
Freedom of God's word: toward an evangelical dogmatics of scripture / Daniel J. Treier -- In many and various ways: hearing the voice of God in scripture / Stephen Fowl -- Hearing God speak from the first testament / John Goldingay -- Voice of God in Israel's wisdom literature / Amy Plantinga Pauw -- That was then, this is now: reading Hebrews retroactively / Myk Habets -- Paths beyond tracing out: the hermeneutics of metaphor and theological method / Erin M. Heim -- Voice of God in historical biblical criticism / Jason McMartin and Tim Pickavance -- Postmodern historical criticism and the possibility of hearing God / William Abraham -- Reading scripture in our context: double particularity in Karl Barth's actualistic view of scripture / Daniel D. Lee -- For the love of God: scripture and the formation of human identity / Ryan S. Peterson.
Proceedings of the fourth Los Angeles Theology Conference (LATC) in January 2016.
Includes bibliographical references and index.
Keywords: Bible -- Theology; Word of God (Christian theology)